1976
DOI: 10.1159/000180733
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Indomethacin on Kidney Function and Plasma Renin Activity in Man

Abstract: 125Iothalamate and 131I-hippuran clearances, sodium excretion and plasma renin activity (PRA) before and during indomethacin administration in an oral dose of 3 × 50 mg/day were studied in volunteers with a normal or reduced kidney function, as well on non-sodium-restricted as on sodium-restricted diet. Indomethacin induced a temporary sodium and water retention and a decrease in glomerular filtration rate. It also lowered PRA. The latter phenomenon did not depend on sodium retention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
4

Year Published

1978
1978
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(87 citation statements)
references
References 12 publications
7
76
4
Order By: Relevance
“…In fact, the initial NO synthesis inhibition at a perfusion pressure of 125 ± 5 mmHg was followed by a significant decrease in TRBF as well as RMBF. In contrast to the effects observed after the blockade of NO synthesis, the inhibition of PG synthesis is followed by a marked reduction of renal blood flow when perfused at low, but not at high RPP levels (5,7,16,19). This is in agreement with our results showing that PG inhibition did not alter TRBF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, the initial NO synthesis inhibition at a perfusion pressure of 125 ± 5 mmHg was followed by a significant decrease in TRBF as well as RMBF. In contrast to the effects observed after the blockade of NO synthesis, the inhibition of PG synthesis is followed by a marked reduction of renal blood flow when perfused at low, but not at high RPP levels (5,7,16,19). This is in agreement with our results showing that PG inhibition did not alter TRBF.…”
Section: Discussionsupporting
confidence: 91%
“…There is, at present, a well accepted notion that PGs (9,10) and NO (5,16,17) play an important role in the regulation of TRBF. In fact, previous studies have shown that the blockade of either NO or PG is followed by a decrease in TRBF and impairment in urine sodium excretion both under basal conditions (5,6) and during pressureinduced natriuresis (6,7,18).…”
Section: Discussionmentioning
confidence: 99%
“…In salt deplete humans, indomethacin has been reported to have little effect on basal renal haemodynamics (Donker et al, 1976;Mackay et al, 1984;Sedor et al, 1984), but there are reports of a significant decrease (Kramer et al, 1985). There is little information available on the renal haemodynamic effect of ibuprofen.…”
Section: Introductionmentioning
confidence: 99%
“…<4 Nevertheless, the effects of longterm treatment on renal hemodynamics resemble those found in studies of short-term treatment in that antiinflammatory drugs seem to have more effect on glomerular filtration rate than on renal blood flow. 39 -44 - VOL 8, No 8, AUGUST 1986 The different effects exerted by anti-inflammatory drugs on renal hemodynamics after short-term and long-term treatment may be partly explained by the studies of Vallatton et al, 21 who reported significant qualitative differences in the effect of indomethacin on renal function, depending on whether anti-inflammatory drugs were administered simultaneously or after the production of a negative sodium balance.…”
Section: -L0mentioning
confidence: 99%